ANALISIS MATERI GERAK PADA TUMBUHAN DALAM BUKU TEKS IPA SMP/MTS KELAS VIII - Dias Idha Pramesti (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2014)
The aim of this article was to determine in appropriate information son the plant movement material found in textbooks IPA SMP/MT seighth grade, the extent of its congruence and provide improvement on the necessary repairs. Analysis of the material was done by examining 5 textbooks easily found in bookstores, especially on the plant movement subject. Further information in the book is confirmed by the latest issue of biology textbooks that are often used as a source of reference material.The analysis showed that on 3 existing textbooks there is some not appropriate information with the concept in biology textbooks, especially about tacticmovement.Examples are given in the textbook IPA SMP / MTs eighth grade is not appropriate with the coverage of meaning plant because the sample of organisms that perform tacticmovement included in protists and if it refers to six-kingdom classification system can not be categorized as plant. Keywords :text book, plant movement, tactic movement